Pengaruh Kualitas Pelayanan terhadap Kepuasan Pelanggan dan Dampaknya terhadap Loyalitas Pelanggan pada Style Leather Collections - Rohimat Nurhasan (Jurnal Wacana Ekonomi, 2016)
Background research is to determine the effect of Service Quality (X) on Satisfaction (Y) and its impact on Loyalty (Z) on Style Leather Collections in Sukaregang Garut. In this study using descriptive and associative analysis methods. The respondents in this study were 96 respondents using purposive sampling method with a sample criteria that had made purchases more than once. The analysis technique used in this research is validity test, reliability test and path analysis. The results of the study state that there is a positive and significant influence of Service Quality Variables on customer satisfaction, meaning that the company is able to improve work discipline by increasing the quality of service provided by the company through employees, there is a positive and significant influence. increasing the quality of service provided by the company through its employees and there is a positive and significant influence of customer satisfaction on customer loyalty, meaning that the company is able to increase customer loyalty by increasing customer satisfaction provided by employees.